Idiopathic Lymphocele: A Possible Diagnosis for Infraclavicular Masses - Adenauer Marinho de Oliveira Góes Junior; Salim Abdon Haber Jeha (Case Reports in Surgery)
Lymphoceles are usually related to trauma or surgery, and its spontaneous development is rare. The aim of this paper is to report an uncommon case of idiopathic lymphocele located on the right infraclavicular region, in a female patient with no previous local trauma or surgery and unremarkable medical history. The diagnose was suggested by the tomographic aspect of the lesion and confirmed by ultrasound-guided fluid aspiration and cytological analysis. The authors also provide a brief review of the most important thing diagnostic features and treatment options for this condition. For the practicing clinician, the most important is to achieve an accurate diagnose and to choose the proper therapeutic method according to each clinical scenario.